2013
DOI: 10.1007/s11356-013-1931-3
|View full text |Cite
|
Sign up to set email alerts
|

Pacific oyster (Crassostrea gigas) hemocyte are not affected by a mixture of pesticides in short-term in vitro assays

Abstract: Pesticides are frequently detected in estuaries among the pollutants found in estuarine and coastal areas and may have major ecological consequences. They could endanger organism growth, reproduction, or survival. In the context of high-mortality outbreaks affecting Pacific oysters, Crassostrea gigas, in France since 2008, it appears of importance to determine the putative effects of pesticides on oyster susceptibility to infectious agents. Massive mortality outbreaks reported in this species, mainly in spring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 46 publications
0
14
2
Order By: Relevance
“…Fourteen pesticides belonging to 4 pesticide groups (herbicides, fongicides, insecticides and molluscicides) were selected based on their detection in the aquatic environment in Britany and Charente Maritime [ 20 ] and their immunotoxic potential for invertebrates. The mixture of the 14 selected pesticides consisted of carbaryl, fosetyl aluminium, alachlor, métolachlor, glyphosate, atrazine, terbuthylazine, diuron, AMPA, bentazon, tebuconazol, imidacloprid, mancozeb and metaldehyde [ 21 ] ( Table 1 ). Solvents were used as recommended by manufacturers ( Table 1 ) and final solvent concentration was less than 0.5% in order to avoid effects of the solvent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen pesticides belonging to 4 pesticide groups (herbicides, fongicides, insecticides and molluscicides) were selected based on their detection in the aquatic environment in Britany and Charente Maritime [ 20 ] and their immunotoxic potential for invertebrates. The mixture of the 14 selected pesticides consisted of carbaryl, fosetyl aluminium, alachlor, métolachlor, glyphosate, atrazine, terbuthylazine, diuron, AMPA, bentazon, tebuconazol, imidacloprid, mancozeb and metaldehyde [ 21 ] ( Table 1 ). Solvents were used as recommended by manufacturers ( Table 1 ) and final solvent concentration was less than 0.5% in order to avoid effects of the solvent.…”
Section: Methodsmentioning
confidence: 99%
“…Assays were carried out to study the effect of the pesticide mixture in vitro on viral (OsHV-1) suspension [ 22 ]. Three concentrations of pesticide mixture were tested (1X, 10X and 200X) [ 21 ] with a 24 hour exposition at 15°C in the dark.…”
Section: Methodsmentioning
confidence: 99%
“…Molluscan haemocytes are known to synthesize MT after Cd exposure as a protection mechanism against metal toxicity (Roesijadi et al 1997;Langston and Bebianno 1998). Another study carried out with pesticides showed no significant effect of a mixture of 14 pesticides and methaldehyde alone tested at different concentrations (according to flow cytometry) on Pacific oyster haemocytes maintained in vitro for short-term periods (2, 4 and 21 h) (Moreau et al 2014). Gagnaire et al (2003) reported no effect on cell viability in Pacific cupped oyster haemocytes exposed to atrazine in vitro.…”
Section: Cell Viabilitymentioning
confidence: 97%
“…Katsumiti et al (2014) showed that phagocytosis was not modified in M. galloprovincialis haemocytes exposed to ionic Cd. Similarly, no significant effect of a mixture of 14 pesticides, tested at different concentrations, on the phagocytic activity of C. gigas haemocytes was observed (Moreau et al 2014). Thus, for a given contaminant, the responses of immunological biomarkers like phagocytosis are sometimes contradictory since the effects can range from almost total immunodepression to immunostimulation, including no effect .…”
Section: Phagocytosis Activitymentioning
confidence: 98%
“…Aquatic organisms are generally very sensitive to pesticides, and it is therefore important to study the impact of molecule alone or in combination to detect possible synergistic action. Moreau et al (2013) from the Institut Français pour la Recherche et l'Exploitation de la Mer (Ifremer) of La Tremblade and Nantes showed that Pacific oyster (Crassostrea gigas) hemocytes are not affected by a mixture of 14 pesticides or metaldehyde alone in shortterm in vitro assays. They conclude that it could be assumed that these oyster cells were resistant to pesticide exposure in tested conditions, and developing in vivo assays appears necessary to better understand the effects of pollutants on immune system in mollusks.…”
mentioning
confidence: 99%